Evaluation of muscle strength following peripheral nerve surgery: A scoping review. Issue 3 (5th May 2021) - McGillivray, Meghan K.; Haldane, Chloe; Doherty, Christopher; Berger, Michael J.
Abstract: Peripheral nerve injury (PNI) can result in devastating loss of function, often with poor long‐term prognosis. Increased use of peripheral nerve surgical techniques (eg, nerve transfer, nerve grafting, and nerve repair) has resulted in improved muscle strength and other functional outcomes in patients with PNI. Muscle strength has largely been evaluated with the British Medical Research Council (MRC) scale. MRC is convenient to use in clinical settings, but more robust measures of muscle function are necessary to fully elucidate patient recovery. This scoping review aims to examine alternative instruments used to assess muscle function in studies of peripheral nerve surgery for PNI of the upper and lower limbs. A scoping review was conducted using Ovid MEDLINE, CINAHL, EMBASE, and PubMed databases in May and December of 2020, yielding a total of 20 studies pertaining to the review question. Studies pertaining to handheld dynamometry, grip and pinch dynamometry, Rotterdam Intrinsic Hand Myometers, isokinetic dynamometry, ultrasonography, and electromyography were reviewed. We provide a synopsis of each method and current clinical applications and discuss potential benefits, disadvantages, and areas of future research.